The Role Of Law Enforcement Intelligence In Prosecutor's Office On "Prosecutor Guards The Village" Program At The North Padang Lawas District Prosecutor's Office - T. Ikhsan Ansyari Husny; Suci Ramadani; Muhammad Arif Sahlepi (Journal Evidence Of Law, 2026)
This study was motivated by the issuance of Attorney General Instruction No. 5 of 2023 concerning the Optimization of the Role of the Attorney General's Office in Building Legal Awareness in Rural Communities through the Village Guard Program (Jaga Desa). The research questions are: How does the Law Enforcement Intelligence Function based on Attorney General Instruction No. 5 of 2023 build legal awareness among rural communities through the Jaga Desa program. What are the efforts and obstacles in implementing the Attorney General's Office's Law Enforcement Intelligence Function in the Jaga Desa program in North Padang Lawas Regency. This research method is through empirical juridical research with field studies at the North Padang Lawas District Attorney's Office. The data collection technique used by the author in this study is field research, covering data sourced from interviews with the Head of Section at the North Padang Lawas District Attorney's Office. The data analysis used in this study is qualitative analysis. The results of the study show that the North Padang Lawas District Attorney's Office has comprehensively implemented this role through the optimization of cross-sectoral performance. There are obstacles to the implementation of this role, but the North Padang Lawas District Attorney's Office continues to show a strong commitment to building legal awareness in rural communities, preventing violations of the law, and realizing the management of village administration with integrity and humanistic justice in North Padang Lawas Regency.